Development of a Biodegradable Film from Jicama Starch (Pachyrhizus erosus (L.) Urbar) for Plant Bag Application - Theamdee, Pawinee; Sooksamran, Kawinna (RMUTP Research Journal Sciences and Technology, 2020)
This research aimed to study the production of a biodegradable film from Jicama starch (Pachyrhizus erosus (L.) Urbar) for plant bag application. The film was prepared by dissolving Jicama starch in water to the concentration of 5 wt%. To study the effect of the glycerol content, the glycerol was added at 6 levels; 0, 10, 20, 30, 40, 50 and 60 wt%. The film was casted in a molded and dried at 60 oC for 24 h. After drying, properties of films; thickness, water activity (aw), solubility, tensile strength (TS), elongation (%E), puncture strength and the degradation of the films were evaluated. The thickness of the films was in the range of 0.16-0.28 mm. The aw of films ranged from 0.36-0.49. The water vapor permeability, water solubility, and flexibility of the film increased with the increasing of glycerol content. Tensile and puncture strength of the starch films tended to increased when the glycerol content decrease. After the films were buried under the ground (8-10 cm depth) for 12 weeks, they were degraded by 100%. The Jicama starch film with 40 wt% glycerol showed the best overall properties.